Silibinin protects human endothelial cells from high glucose‐induced injury by enhancing autophagic response. Issue 10 (26th June 2018) - Rezabakhsh, Aysa; Fathi, Farzaneh; Bagheri, Hesam Saghaei; Malekinejad, Hassan; Montaseri, Azadeh; Rahbarghazi, Reza; Garjani, Alireza
Abstract: Silibin, a flavonoid from the seeds of Silybum marianum (L.) Gaertn. (Asteraceae) has been reported to produce curative properties in diabetes. Autophagy is generated by a vast array of insults for removal of damaged proteins and organelles from the cell. Inadequate autophagy promotes endothelial cells dysfunction and delays in diabetic ulcers recovery. We hypothesized that silibinin could protect endothelial cells against high glucose‐induced damage by engaging autophagic responses. HUVECs viability was evaluated by MTT assay. The Griess method and TBARS assay were used to monitor changes in the levels of nitric oxide and malondialdehyde, respectively. ROS generation was recorded in DCFDA‐stained cells analyzed by flow cytometry. To investigate the role of silibinin on migration, we used scratch test. The level of autophagy proteins LC3, Becline‐1, and P62 were measured by Western blotting. Our data showed that silibinin had potential to increase cell survival after exposure to high glucose condition. Total levels of oxidative stress markers were profoundly reduced and the activity of GSH was increased by silibinin. High glucose suppressed HUVECs migration to the scratched area. However, a significant increase in cell migration was observed after exposure to silibinin. Autophagy was blocked at the late stage by high glucose concentration and silibinin initiated an autophagic response by reducing P62 and enhancing Beclin‐1 and LC3‐II‐LC3‐I ratio. These effects were blocked by autophagy inhibitor of 3‐Methyladenine. These observations suggest that silibinin could protect HUVECs from high glucose induced‐damage possibly by activation of autophagy pathway. Abstract : This manuscript highlighted therapeutic potential of phyto‐compound Silibinin on human endothelial cells by engaging autophagy signaling pathway.